The Decision to Flee: Analyzing Gender-Specific Determinants of International Refugee Migration - Lena Schmid; Laura Renner (ZBW - Leibniz Information Centre for Economics, 2020)
Using a gravity approach, we explore determinants and dynamics of refugee migration using a gendered cross-national dyadic dataset on refugee movements for the years 2000-2015. Along three dimensions (push, pull and cost factors), we analyze whether there are heterogeneous effects of ight determinants for men and women. Our results suggest that within the push dimension there is only little difference in gender-specific responses. Most prominently, women react relatively stronger to the existence of sexual violence as a con ict strategy. When it comes to dyadic factors, we find that distance is a decisive factor for men and women. The most gender-sensitive dimension appears to be the pull factors: Neighboring countries attract more women in comparison to men as well as to non-neighbors. For non-neighbors, female ows are more sensitive to political stability, women's rights and the economic situation of the destination
Keywords: F22; 330; Refugees; International Migration; Distance; Conflict; Gender